2015
DOI: 10.1038/ncomms7042
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant splicing of U12-type introns is the hallmark of ZRSR2 mutant myelodysplastic syndrome

Abstract: Somatic mutations in the spliceosome gene ZRSR2 — located on the X chromosome — are associated with myelodysplastic syndrome (MDS). ZRSR2 is involved in the recognition of 3΄ splice site during the early stages of spliceosome assembly; however, its precise role in RNA splicing has remained unclear. Here, we characterize ZRSR2 as an essential component of the minor spliceosome (U12-dependent) assembly. shRNA mediated knockdown of ZRSR2 leads to impaired splicing of the U12-type introns, and RNA-Sequencing of MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
246
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 212 publications
(275 citation statements)
references
References 69 publications
19
246
0
5
Order By: Relevance
“…ZRSR2 is an essential component of this minor spliceosome. Impaired splicing of the U12-type introns have been observed after shRNA-mediated knockdown of ZRSR2 and in ZRSR2-mutated samples [55]. Recent work [56] suggested that U2 snRNPs components interact with chromatin, independently of RNA.…”
Section: Mutations Of the Sf3b1 Gene And Rna Biologymentioning
confidence: 99%
“…ZRSR2 is an essential component of this minor spliceosome. Impaired splicing of the U12-type introns have been observed after shRNA-mediated knockdown of ZRSR2 and in ZRSR2-mutated samples [55]. Recent work [56] suggested that U2 snRNPs components interact with chromatin, independently of RNA.…”
Section: Mutations Of the Sf3b1 Gene And Rna Biologymentioning
confidence: 99%
“…However, the U2AF 35 mutations alter specific ZnK residues, whereas the URP mutations are randomly distributed throughout the protein sequence and often null. This difference most likely reflects the distinct functions of the two proteins: U2AF 35 recognizes the intron-exon junction of the major class of splice sites in conjunction with U2AF 65 (Merendino et al 1999;Wu et al 1999;Zorio and Blumenthal 1999), as opposed to a selective role for URP in a "minor," stress-associated class of intron splicing (Shen et al 2010;Madan et al 2015). Yet, no U2AF 65 paralog has been identified as a ULM partner for the URP UHM to date.…”
Section: Do Uhms Bind Rna?mentioning
confidence: 99%
“…Puzzling, however, is the observation that mutations in SRSF2 and U2AF1 appear to associate with poor prognosis of the disease while mutations in SF3B1 seem to predict good prognosis (Papaemmanuil et al 2011). ZRSR2 was reported as an essential component of the minor spliceosome (U12 dependent) assembly (Madan et al 2015), which is the least frequent compared to the mutation frequencies of the other three splicing factor genes. As the functions of these splicing factors converge on the definition of 3 ′ splice sites, a popular hypothesis is that mutations in these genes may affect a common set of splicing events that may directly contribute to MDS.…”
Section: Altered Splicing Programs By Splicing Factor Mutations In Mdsmentioning
confidence: 99%